Densification mechanism during hot-pressing of single-phase zirconium boride powders with different dislocation density. Issue 13 (1st July 2022) - Li, Xiao-Ning; Wang, Xing-Ming; Bai, Xue; Liu, Yu-Yang; Gui, Tao; Wang, Xing-Qi; Xue, Zhong-Yuan; Wen, Jian-Kang
Abstract: ZrB2 powders with different dislocation density were synthesised by the self-propagating high-temperature synthesis (SHS) and carbothermal reduction (CTR) method. The defect structure was analysed by transmission electron microscopy (TEM), and the dislocation density was determined though the convolutional multiple whole profile fitting (CMWP-fit). The SHS process exhibited a very high rate of heating and cooling, which introduces a higher dislocation density (8.68 × 10 15  m -2 ) due to thermal stresses caused by the volume change of crystal, and the crystal grew spirally. Comparably, the CTR process depicted a low rate of heating and cooling. The time was sufficient for crystal nucleation and growth, thus the dislocation density of crystal was lower (6.49 × 10 11  m -2 ), and the crystal grew layer-by-layer. By mixing with the SHS and CTR powders, 5 kinds of powders with different dislocation density were prepared, followed by hot-pressing densification. The dislocation density of powder was calculated and result shows that with the increasing of the content of SHS powder from 0 to 1 the dislocation density increases from 6.49 × 10 11  m -2 to 8.68 × 10 15  m -2, meanwhile the relative density of ZrB2 ceramics increased from 82.1% to 98.1%. The hot-pressing densification can be divided into two stages. In the pre-sintering stage, with increasing of dislocation density of the powders, the densification mechanism changes from bulk diffusion to grain boundary diffusion, and all are of the dislocation-climb mechanism in the post-sintering stage.